The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2007
DOI: 10.2138/am.2007.2414
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of defects and the local structure in natural and synthetic alunite (K, Na, H3O)Al3(SO4)2(OH)6 by multi-nuclear solid-state NMR spectroscopy

Abstract: The local structural environments in a series of natural and synthetic alunite samples [ideally AAl 3 (SO 4 ) 2 (OH) 6 , A = H 3 O + , D 3 O + , Na + , and K + ] have been probed by solid-state 1 H, 2 H, 23 Na, 27 Al, and 39 K NMR spectroscopy. The natural alunite [KAl 3 (SO 4 ) 2 (OH) 6 ] and synthetic hydronium alunite samples contain few structural defects, whereas the synthetic natroalunite and alunite samples have ca. 10% Al vacancies based on 27 Al NMR. A new 27 Al local environment (Al D ) was observed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

12
60
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 25 publications
(72 citation statements)
references
References 43 publications
12
60
0
Order By: Relevance
“…The most recent study done by Nielson et al (2007) found that H 3 O + is not found in alunite or natroalunite in solid state NMR studies that have both A and B site deficiencies. They did see evidence for H 3 O + in hydronium alunite.…”
Section: Hydronium In the Jarosite Groupmentioning
confidence: 99%
See 4 more Smart Citations
“…The most recent study done by Nielson et al (2007) found that H 3 O + is not found in alunite or natroalunite in solid state NMR studies that have both A and B site deficiencies. They did see evidence for H 3 O + in hydronium alunite.…”
Section: Hydronium In the Jarosite Groupmentioning
confidence: 99%
“…They did see evidence for H 3 O + in hydronium alunite. Nielson et al (2007) postulated that vacancies in the B site are compensated by the addition of 4 H + ions, resulting in 4 Al-OH 2 bonds per vacancy. This substitution is accompanied by deprotonation of H 3 O + in the A site, forming H 2 O, which is then unnecessary for charge balance resulting in an A site vacancy.…”
Section: Hydronium In the Jarosite Groupmentioning
confidence: 99%
See 3 more Smart Citations